The deubiquitinase Otub1 controls the activation of CD8+ T cells and NK cells by regulating IL-15-mediated priming - Zhou, Xiaofei; Yu, Jiayi; Cheng, Xuhong; Zhao, Baoyu; Manyam, Ganiraju C.; Zhang, Li; Schluns, Kimberly; Li, Pingwei; Wang, Jing; Sun, Shao-Cong (Nature immunology, 2019)
CD8 + T cells and natural killer (NK) cells are central cellular components of immune responses against pathogens and cancer, which rely on interleukin (IL)-15 for homeostasis. Here we show that IL-15 also mediates homeostatic priming of CD8 + T cells for antigen-stimulated activation, which is controlled by a deubiquitinase, Otub1. IL-15 mediates membrane recruitment of Otub1, which inhibits ubiquitin-dependent activation of AKT, a kinase that is pivotal for T cell activation and metabolism. Otub1 deficiency in mice causes aberrant responses of CD8 + T cells to IL-15, rendering naive CD8 + T cells hypersensitive to antigen stimulation characterized by enhanced metabolic reprograming and effector functions. Otub1 also controls the maturation and activation of NK cells. Deletion of Otub1 profoundly enhances anticancer immunity by unleashing the activity of CD8 + T cells and NK cells. These findings suggest that Otub1 controls the activation of CD8 + T cells and NK cells by functioning as a checkpoint of IL-15-mediated priming. IL-15 has important functions in the activation and homeostasis of cytotoxic T lymphocytes (CTLs) and NK cells. Sun and colleagues demonstrate that the deubiquitinase Otub1 controls CTLs and NK cells in a cell-intrinsic manner by negatively regulating IL-15 signaling.